The Effect of The Contextual Teaching And Learning (CTL) Model on The Reading Literacy Ability of Grade V at State Elementary School 1 Arjawinangun - Azhahra, Rahma Ayuzuana; Jannah, Widia Nur; Hanikah, Hanikah (FKIP - Universitas Riau, 2025)
Reading literacy is a fundamental competency that supports students’ success in elementary education. Nevertheless, international studies such as PISA and PIRLS consistently report that Indonesian students’ reading literacy levels are still low. This condition highlights the need for innovative learning models that connect material with students’ real-life contexts, making the learning process more meaningful. One suitable approach is the Contextual Teaching and Learning (CTL) model. This study aimed to examine the effect of implementing the CTL model, supported by the Enuma School application, on the reading literacy skills of fifth-grade students at State Elementary School 1 Arjawinangun. The research employed a quantitative approach with a One Group Pretest-Posttest design involving 39 students. Instruments included a reading literacy test, observation sheets, and student questionnaires. Data were analyzed through validity and reliability testing, paired-sample t-tests, and effect size calculations. The findings revealed a significant improvement in students’ reading literacy after the implementation of CTL. Posttest scores were notably higher than pretest scores, with a large effect size. Observation and questionnaire results also indicated that students became more engaged, motivated, and showed positive attitudes toward reading. Thus, the CTL model, supported by digital applications, proves effective in enhancing elementary students’ reading literacy.